Power Curve Evaluation of Micro-Scale Turbines for Harvesting Wind Energy in Malaysia - Abbas D.U.; Tiong S.K.; Alkahtani A.A.; Chen C.P.; Alkawsi G.; Ekanayake J. (Natural Sciences Publishing, 2023)
With wind energy gaining significant importance in recent years, many countries aspire to harvest this clean and cheap energy. In Malaysia, this goal is affected by slow wind speeds, which usually hinder the installation of wind turbines across the country. In this paper, we conduct a simulation study of the factors that affect wind power generation for several turbines. We use the power curves of five wind turbines (WTs) and compare their production with real wind speed data gathered from Sepang and Mersing regions of Malaysia as a case study. The data were recorded at a 15 m height from the ground level by the Malaysian Meteorological Department (MMD) throughout the year 2015. We fix the rated power of the turbines at 400 W, change the lengths of the turbine blades, and calculate the amount of energy produced in the two regions with reference to the turbines cut-in speeds of 4.0, 3.5, 3.0, 2.5, and 2.0 ms1, which correspond to turbine blade length (BL) of 0.62, 0.71, 0.82, 0.96, and 1.14 m, respectively. The results indicate that the amount of energy produced depends on the rated power, length of the turbine blade, rated and cut-in speeds of the turbine, and the characteristics of the wind speed in the area. We found that for one turbine, the highest annual energy rates that could be harvested were 357.5 and 373.15 kWh/year at a cut-in speed of 2 ms1, with total annual revenue generation (ARG) values of RM 201.0 and RM 193.50 during 6.95- and 7.25-year payback periods (PBP), respectively, in Mersing and Sepang. This study is the first of its kind to calculate the amount of energy produced using small-capacity wind turbines at different cut-in speeds and with different BLs. This study establishes the guidelines for a new era of small WTs in Malaysia and other countries with similar wind speeds. 2021. NSP Natural Sciences Publishing Cor. All Rights Reserved.